2019
DOI: 10.29121/granthaalayah.v7.i8.2019.695
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antidiabetic Activity and Mechanism of Action of Three Cameroonian Medicinal Plant Extracts

Abstract: The aim of the present work is to study and compare antidiabetic activity of extracts from Catharentus roseus, Persea americana, and Eucalyptus globulus as well as their mechanism of action. The aqueous and methanolic plant extracts were respectively prepared by decoction and maceration. The phytochemical screening was done by standard methods. The extracts were subsequently tested in vivo on Wistar albino rats (Rattus norvegicus) with temporary hyperglycemia. The methanolic extract of P. americana leaves show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Similarly, for P. americana (Njateng et al, 2018) in an in vitro study showed that methanol extract from leaves of P. Americana Mill strongly inhibits alpha-glucosidase, maltase-glucoamylase, aldose reductase and aldehyde reductase and showed almost no effect against beta-glucosidase. Also, Chimi et al (2019) carried out an in vivo study where it was shown that the methanol and aqueous extracts of the leaves of P. Americana have high antidiabetic activities with 150 mg/Kg as the best dosage. These above results probably justify why these plants species are used in folk medicine for the treatment of diabetes, and suggest validity of the formulated antidiabetic drugs presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for P. americana (Njateng et al, 2018) in an in vitro study showed that methanol extract from leaves of P. Americana Mill strongly inhibits alpha-glucosidase, maltase-glucoamylase, aldose reductase and aldehyde reductase and showed almost no effect against beta-glucosidase. Also, Chimi et al (2019) carried out an in vivo study where it was shown that the methanol and aqueous extracts of the leaves of P. Americana have high antidiabetic activities with 150 mg/Kg as the best dosage. These above results probably justify why these plants species are used in folk medicine for the treatment of diabetes, and suggest validity of the formulated antidiabetic drugs presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, which are well-known to be potent antioxidants and may help protect organs against toxicity or oxidative stress caused by substances like alloxan, have been shown to be an active component in many herbal medications [21,22]. The plant extract's apparent hypoglycaemic activity may have been influenced by saponins, which have been found to exhibit hypoglycaemic activity [23]. This activity may be caused by the suppression of liver glycogenesis or glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ngwaka Tb [48] In vivo rat: 37.5-150 mg/kg [49] Chromolaena corymbosa (Aubl.) R. M. King and H. Rob.…”
Section: Fulelementioning
confidence: 99%